Antimicrobial Biomaterials for Chronic Wound Care - Miron, Adrian; Giurcaneanu, Calin; Mihai, Mara Madalina; Beiu, Cristina; Voiculescu, Vlad Mihai; Popescu, Marius Nicolae; Soare, Elena; Popa, Liliana Gabriela (Pharmaceutics, 2023)
Chronic wounds encompass a myriad of lesions, including venous and arterial leg ulcers, diabetic foot ulcers (DFUs), pressure ulcers, non-healing surgical wounds and others. Despite the etiological differences, chronic wounds share several features at a molecular level. The wound bed is a convenient environment for microbial adherence, colonization and infection, with the initiation of a complex host–microbiome interplay. Chronic wound infections with mono- or poly-microbial biofilms are frequent and their management is challenging due to tolerance and resistance to antimicrobial therapy (systemic antibiotic or antifungal therapy or antiseptic topicals) and to the host’s immune defense mechanisms. The ideal dressing should maintain moisture, allow water and gas permeability, absorb wound exudates, protect against bacteria and other infectious agents, be biocompatible, be non-allergenic, be non-toxic and biodegradable, be easy to use and remove and, last but not least, it should be cost-efficient. Although many wound dressings possess intrinsic antimicrobial properties acting as a barrier to pathogen invasion, adding anti-infectious targeted agents to the wound dressing may increase their efficiency. Antimicrobial biomaterials may represent a potential substitute for systemic treatment of chronic wound infections. In this review, we aim to describe the available types of antimicrobial biomaterials for chronic wound care and discuss the host response and the spectrum of pathophysiologic changes resulting from the contact between biomaterials and host tissues.